SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI FAKULTAS PETERNAKAN UNIVERSITAS JAMBI - Nurjani, Yeni; Firdaus, Dyoza (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2020)
Library Information System is one of the things that was developed so that students can ease in terms of borrowing books online. Therefore, by providing various facilities aimed at facilitating students in finding various information needed from the library before lending. The main elements in forming a system consists of inputs, processes and outputs, while the input needed from this system is member data and data books. Process the data or process it into a report that will be submitted to the library leadership. This website is created using the PHP Web Programming Language and uses MySQL for its database which is equipped with member tables, book tables and loan tables. The Web-Based Library Information System at the Faculty of Animal Husbandry at the University of Jambi is used as a means of information and loans for students, a tool for processing data for employees or administration at the Library of the Faculty of Animal Husbandry in the University of Jambi.